Impact of Biochar on Yield and Nutrient Conservation in the Sunflower (Helianthus annuus L.) Field in Non-Saline Tidal Ecosystem: Impact of biochar on yield and nutrient in sunflower (South Asian Journal of Agriculture, 2023)
Biochar is an organic amendment produced by pyrolysis used in soil to conserve soil nutrients. Research work was conducted to observe the effect of biochar on yield and nutrient conservation ability in non-saline land of southern Bangladesh. The research comprised four different soil treatments as 0, 5, 10, and 20 t ha-1biochar along with recommended doses of fertilizers. Biochar @ 20 t ha-1 with a combination of fertilizers showed the maximum yield (3.37 t ha-1). The highest amounts of K, Na, Ca, Mg, S, and P were obtained from biochar-treated plots of 20 t ha-1. The control plots showed the lowest yield and the lowest amount of K, Na, Ca, Mg, S and P. Biochar @ 20 t ha-1 with a combination of fertilizers could be recommended for higher yield and nutrient conservation in the southern non-saline area of Bangladesh.South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 64-71